2023
DOI: 10.3390/cancers15061752
|View full text |Cite
|
Sign up to set email alerts
|

A Handheld Visible Resonance Raman Analyzer Used in Intraoperative Detection of Human Glioma

Abstract: There is still a lack of reliable intraoperative tools for glioma diagnosis and to guide the maximal safe resection of glioma. We report continuing work on the optical biopsy method to detect glioma grades and assess glioma boundaries intraoperatively using the VRR-LRRTM Raman analyzer, which is based on the visible resonance Raman spectroscopy (VRR) technique. A total of 2220 VRR spectra were collected during surgeries from 63 unprocessed fresh glioma tissues using the VRR-LRRTM Raman analyzer. After the VRR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…For instance, Michael et al ( 54 ) developed a handheld contact Raman spectroscopy probe technique for live, local detection of cancer cells in the human brain with a sensitivity of 93% and a specificity of 91%. Zhang et al ( 23 ) investigated human glioma using a portable visible resonance Raman analyzer under quasiclinical conditions with over 80% accuracy. Kevin et al ( 55 ) for the first time developed a Raman spectroscopy guidance system in human in vivo integrated with a brain biopsy needle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Michael et al ( 54 ) developed a handheld contact Raman spectroscopy probe technique for live, local detection of cancer cells in the human brain with a sensitivity of 93% and a specificity of 91%. Zhang et al ( 23 ) investigated human glioma using a portable visible resonance Raman analyzer under quasiclinical conditions with over 80% accuracy. Kevin et al ( 55 ) for the first time developed a Raman spectroscopy guidance system in human in vivo integrated with a brain biopsy needle.…”
Section: Discussionmentioning
confidence: 99%
“…AI algorithms have been shown to improve the robustness of Raman spectroscopy-based precise cancer diagnosis ( 22 ). Particularly, previous studies have demonstrated the capability of Raman spectroscopy in intraoperative brain cancer detection ( 23–27 ). Regarding molecular subgrouping, most Raman spectroscopy studies focused on detection of IDH mutation, the accuracy of which ranged from 80 to 90% ( 28–30 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can help a surgical doctor to better remove the tumor and achieve total resection. In our previous studies, a Raman technique called visible resonance Raman (VRR) spectroscopy was shown to be promising as an optical molecular diagnostic technique for rapid noninvasive intraoperative diagnosis of glioma tumors among other human tumors [4][5][6][7][8]. Machine learning analysis along with decomposition methods has been used to analyze and classify spectral data and yielded high accuracy in distinguishing cancerous from healthy tissue or cells [4,5,7,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, a Raman technique called visible resonance Raman (VRR) spectroscopy was shown to be promising as an optical molecular diagnostic technique for rapid noninvasive intraoperative diagnosis of glioma tumors among other human tumors [4][5][6][7][8]. Machine learning analysis along with decomposition methods has been used to analyze and classify spectral data and yielded high accuracy in distinguishing cancerous from healthy tissue or cells [4,5,7,[9][10][11][12][13][14]. However, when Raman spectra are classified, preprocessing such as baseline subtraction has been part of the standard procedure which usually involves tuning fitting parameters.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the practical potential of this method in combination with supervised and unsupervised machine learning algorithms has been shown not only for the classification of tumor types and distinct histomorphological tumor areas but also for the differentiation of the tumor grade or the detection of tumor margins/infiltration zone [4][5][6][7]. Most recently, Zhang et al yielded >80% accuracy with support vector machinebased intraoperative differentiation of glioma tissue and healthy control, and Romanishkin et al reported a support vector machine-based accuracy in detecting glioblastoma tissue (regardless of the histologically proven sampling area, namely, central tumor core or tumor edge) of 83% [8,9]; by using unprocessed samples of pediatric brain tumors, even an accuracy of 86.2% was achieved when classifying between low-grade gliomas and normal brain by employing a logistic regression model [10]. Although, commonly, fresh tissue specimens are spectroscopically examined intraoperatively in vivo [11] by using a handheld Raman probe or ex vivo [4,12] by using advanced Raman imaging techniques, e.g., Stimulated Raman Histology, other approaches aim to establish RS on formalin-fixed or formalin-fixed and paraffin-embedded (FFPE) tissue.…”
Section: Introductionmentioning
confidence: 99%